Analysis on Fatigue Recognition System Using Facial Features and HRV - Vijayprasath, S.; Prasanth, A.; Athal, I.; kathirvel, M. (International Journal of Engineering and Technology, 2018)
Observing the driver's state of cognizance and weakness is totally important to diminish the amount of road accidents. A simple approach cognitive approach for inspection of driver safety levels by combining facial features and Heart rate Variability (HRV) is discussed.Fatigue detection is performed through Simulation that involves face detection, face localization, eye detection, thresholding and eye blink detection using Matlab and OpenCV. Heart rate was analysed using Signal Acquisition, Filtering, R-R Peak Interval Extraction and heart rate calculation. The simulation was performed using LabVIEW. A simple modelwas analysed using sensors wrapped into steering wheel and from it if the measured pulse rate is lesser than 65 the system detects it as low heart rate which corresponds to drowsiness detection.Â Â